Ekokritik dan Logika Ekologi Cerpen Ama Nara Karya Silvester Petara Hurit (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to describe Ecocriticism and Ecological Logic of Ama Nara Short Story by Silvester Petara Hurit. This study uses an ecocritic approach with a descriptive qualitative research method. The results of the Ecocriticism and Ecological Logic research of Ama Nara Short Story by Silvester Petara Hurit are as follows, (1) nature is the highest manifestation of Lamaholot society. The ecological logic that being modern in Ama Nara's view does not have to leave nature and ancestors. Ecocriticism of the attitude of the main character of the short story, Ama Nara who is not tempted by the modern lifestyle, (2) the attachment of farmers and nature. Ama Nara's ecological logic to protect the environment, continue to care for the fertility of the soil naturally, and that is actually much more valuable. Ecocriticism lies in Ama Nara's attitude to persist in choices, and (3) empowerment of natural resources. Ama Nara's ecological logic creates a local food barn (hoku) so that food needs are met. Ecocriticism lies in Ama Nara's attitude to remain consistent in maintaining traditional life by continuing to empower existing natural resources that make her family happy.